2018
DOI: 10.7717/peerj.4335
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and social-demographic and obstetric factors associated with postpartum depression: differences among ethnic Han and Kazak women of Northwestern China

Abstract: BackgroundStudies on postpartum depression (PPD) in China have focused primarily on women of Han ethnicity, whereas work on other ethnic groups has proven limited. This study explored the ethnic differences of associated social-demographic and obstetric factors for PPD between Han-majority and Kazak-minority women in northwestern China.MethodsHan and Kazak women who received routine examinations at four hospitals in a multi-ethnic area of China six weeks after childbirth between March 2016 and December 2016 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
(28 reference statements)
2
12
1
Order By: Relevance
“…Our results demonstrated that the proportion of mothers who have PPD based on EPDS outcomes is 16.4% at the sixth week after giving birth, which is in line with the findings of previous studies conducted in other Asian countries . Although this finding is considered to be higher than that among studies conducted in Western countries (13%), it is consistent with international studies, which have estimated between 10% and 41% of women experience PPD after childbirth .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrated that the proportion of mothers who have PPD based on EPDS outcomes is 16.4% at the sixth week after giving birth, which is in line with the findings of previous studies conducted in other Asian countries . Although this finding is considered to be higher than that among studies conducted in Western countries (13%), it is consistent with international studies, which have estimated between 10% and 41% of women experience PPD after childbirth .…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review and meta‐analysis by Shorey et al reported an incidence of PPD at 17% among postpartum women, with a higher prevalence (26%) noted in the Middle East and a lower prevalence (8%) noted in Europe. In Asia, the overall prevalence of PPD has been found to range from 4.4% to 30% by 6 weeks after birth …”
Section: Review Of the Literaturementioning
confidence: 99%
“…For instance, PPD has been found to be a putative cause of disastrous behavioural tendencies, such as suicidal intent [34]. A substantial body of research has reported possible risk factors, e.g., socio-demographic factors, obstetric factors, the course of pregnancy and social support, for the development of postpartum depressive disorders [35][36][37][38][39]. Currently, improving the screening and diagnosis processes for postpartum mental illness, especially the provision of early detection and prevention of postpartum depressive disorders, has been an important task for all health professionals working with women during pregnancy and childbirth [40].…”
Section: Introductionmentioning
confidence: 99%
“…While based on the Confucian paradigm, a woman is expected to take care of and show respect and obedience to her mother-in-law; the mother-in-law, in turn, plays a key role in taking care of the pregnant and parturient woman. Previous studies [46] reported that 48.8% of mothers-in-law were caregivers after delivery among women in China. Undoubtedly, building a favorable relationship between women and their mothers-in-law is one of the keys to reducing the risk of women's PPD.…”
Section: Discussionmentioning
confidence: 96%